An Analytical Solution for Maximum Field Strength at the Pre-fabricated Joints of DC XLPE Cables - Ying LIU; Mingwei ZHAO; Jiawei CHEN (Zhongguo dianli)
Due to the complex structure and multiple composite interfaces of the cable joints, the DC electric field distribution is usually analyzed by means of a numerical simulation software, which uses the electric-thermal coupling method for iterative calculation, and is time-consuming. In order to evaluate the maximum field strength at the joint for medium and low voltage DC XLPE cables, a simplified analytical solution was presented. Based on the theories of heat transfer and electromagnetics, a simplified model was established for analyzing the thermal field distribution at the cable joint, and an analytical formula was derived for calculating the field strength at the foot of the stress cone, with which only a few necessary parameters are needed to determine the maximum field strength at the joint. In this paper, by taking the prefabricated joints of silicone rubber and ethylene-propylene rubber for the 10 kV and 35 kV XLPE cables as an example, analytical calculations were carried out under different DC voltages and temperature differences between the joint inside and outside, and the analytical results were compared with those from the finite element simulation. The consistence between them verifies the accuracy of the proposed analytical solution and its applicability for the design and evaluation of the medium and low voltage DC cable pre-fabricated joints in practical projects.